Do foreign-owned firms provide better working conditions than their domestic counterparts? A comparative analysis - Alexander Hijzen; Pedro Silva Martins; Thorsten Schank; Richard Upward (Institute for the Study of Labor (IZA), 2010)
This paper analyses to what extent working conditions in foreign-owned firms differ from those in their domestic counterparts. It makes three main contributions. First, we replicate the consensus in the empirical literature by applying a standardised methodology to firm-level data for three developed (Germany, Portugal, UK) and two emerging economies (Brazil, Indonesia). We show that, consistent with previous evidence, foreign-owned firms offer substantially higher average wages than domestic firms and that this difference is particularly important in emerging economies. Second, we show that these positive wage effects of foreign takeovers reduce in size when controlling for changes in the composition of the workforce, although they tend to remain positive and statistically significant. However, the wage effects associated with worker movements from domestic to foreign firms are potentially important, particularly in emerging economies. Third, we look not only at wage outcomes but also consider other working conditions such as working hours, job stability and union coverage. We find that foreign takeovers of domestic firms tend to have a small positive effect on wages, but little effect on other aspects of working conditions.
Keywords: F14; F16; F23; 330; foreign direct investment; foreign wage premia